2014
DOI: 10.1038/mt.2014.128
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Administration of Platelets Incorporating Inactivated Sendai Virus Eradicates Melanoma in Mice

Abstract: Tumor microenvironments include a number of fibrin clots due to the microbleeding caused by cancer cell invasion into blood vessels, which suggests the potential utility of a platelet vector for systemic cancer treatment. We previously reported that inactivated Sendai virus (hemagglutinating virus of Japan; HVJ) envelope (HVJ-E) activates anti-tumor immunity and induces cancer cell-selective apoptosis. The hemagglutination activity that blocks the systemic administration of HVJ-E was dramatically attenuated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…We showed that HVJ-E exhibited cytotoxicity against various MM cells but not healthy PBMCs. Human umbilical vein endothelial cells (HUVECs) and human aortic endothelial cells (HAECs) were also treated with HVJ-E, and the proliferation of HUVECs and HAECs was not inhibited (Supplementary Figure 1F–1G), which is consistent with our previous report [31]. …”
Section: Resultssupporting
confidence: 91%
“…We showed that HVJ-E exhibited cytotoxicity against various MM cells but not healthy PBMCs. Human umbilical vein endothelial cells (HUVECs) and human aortic endothelial cells (HAECs) were also treated with HVJ-E, and the proliferation of HUVECs and HAECs was not inhibited (Supplementary Figure 1F–1G), which is consistent with our previous report [31]. …”
Section: Resultssupporting
confidence: 91%
“…Direct intratumoral injection of HVJ-E activates anti-tumor immunity and induces direct cancer killing [2527]. HVJ-E target cells in the TME include cancer cells, macrophages, dendritic cells, fibroblasts and endothelial cells [2528]. As a result, HVJ-E can act as a modulator of the TME for cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…For activation of CTLs, direct presentation of tumor‐associated antigens to CD8 + lymphocytes by DCs is essential in a mouse glioma model using oncolytic adenovirus . Nishikawa et al reported that systemic administration of platelets incorporating inactivated Sendai virus induced the accumulation of CD4 + /CD8 + lymphocytes in mouse melanomas . In their experiments, when CD4 + or CD8 + lymphocytes were depleted, tumor suppression was significantly abrogated, especially in CD8 + lymphocyte‐depleted group.…”
Section: Discussionmentioning
confidence: 99%